Study on structural evolution law of overlying rock mass in fully mechanized top-coal caving face under open-pit slope with extremely thick and hard overburden - Chen, Hanxin; Luan, Mengying; Xue, Mei; Wang, Mingquan; Tian, Hailang; Qu, Yinghao; Yuan, Qiang; Zhang, Mingtian (Frontiers in Earth Science, 2025)
Analyzing overburden movement, surface deformation and fracturing in mines with extremely thick, hard cover is critical for coal mine safety. In this context, the present study examines the 021N2 fully-mechanized top-coal caving face beneath an open-pit slope with extremely thick, hard overburden, developing structural-mechanics models and performing PFC-2D numerical simulations to investigate the structural evolution of the overlying rock mass. The simulations reveal that vertical displacement dominates the slope’s post-mining deformation, and that a force-chain arch forms above the goaf with associated stress fracturing and redistribution. In addition, mining-induced surface fissures create significant air leakage into the goaf, posing a high risk of spontaneous combustion. These findings provide a theoretical basis and technical guidance for controlling thick-overburden caving faces under open-pit slopes, thereby informing safer mining operations and engineering practice in similar contexts.